Role of Biomarkers in Medicine 2016
DOI: 10.5772/62555
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers, Obesity, and Cardiovascular Diseases

Abstract: Obesity and overweight are among the major health problems in the world today. The excessive accumulation of fat in adipose tissue is accompanied by low-grade inflammation, adipokine secretion dysregulation, oxidative stress, and an alteration of the secretion of gut hormones and food intake related to peptides. This is related to the development of cardiovascular diseases, which have been increased worldwide during the last years approximately. The biomarkers are tremendously important to predict, diagnose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 143 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…[51]. Another study also reports eight miRNAs which are found in obese population, that is, PTEN gene (hsa-miR-130b-3p, hsa-miR-142-5p, hsa-miR-148a-3p, hsa-miR-21-5p, hsa-miR23a-3p, hsa-miR-26b-5p, hsa-miR-320a, and hsa-miR-486-5p) [46,47,52]. e early detection of changes in circulating miRNA levels represents a promising strategy for characterizing obesity and to adjust diet.…”
Section: Biomarkersmentioning
confidence: 98%
See 4 more Smart Citations
“…[51]. Another study also reports eight miRNAs which are found in obese population, that is, PTEN gene (hsa-miR-130b-3p, hsa-miR-142-5p, hsa-miR-148a-3p, hsa-miR-21-5p, hsa-miR23a-3p, hsa-miR-26b-5p, hsa-miR-320a, and hsa-miR-486-5p) [46,47,52]. e early detection of changes in circulating miRNA levels represents a promising strategy for characterizing obesity and to adjust diet.…”
Section: Biomarkersmentioning
confidence: 98%
“…So its reduction may be involved in excessive dietary intake and obesity. In contrary, reduction of plasma ghrelin concentration ends with a physiological adaptation to the positive energy balance associated with obesity [47,54].…”
Section: Gut Microbiotamentioning
confidence: 99%
See 3 more Smart Citations